Investigation of Some Long Noncoding RNAs (LncRNAs) in Pediatric Inflammatory Bowel Disease (IBD): An Iranian Study - Fatemeh Khesali; Azizollah Yousefi; Seyyed Amir Yasin Ahmadi; Reza Nekouian (Biochemistry Research International)
Conclusion: It seems that these LncRNAs may have different roles in pediatric IBD. Further studies are needed on pediatric cases of IBD.